Trainee teachers’ observation of learnercentred instruction and assessment as applied by History and Social Sciences teachers (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
A growing body of research shows that the overall quality of teaching and learning is improved when learners have the opportunity to become actively involved in the learning process through which ample opportunities are given to question, apply and consolidate new knowledge. With the dawning of a new South Africa in 1994, more emphasis was placed on learner-centred instruction and assessment which is the reason why policy documents such as the National Curriculum Statement (NCS) and the Curriculum and Assessment Policy Statement (CAPS) endorsed this educational approach. The aim of this study is to investigate through the observation of trainee teachers to what extent History and Social Sciences teachers have adjusted from their predominately traditional educational paradigm of transmitted and absorbed knowledge by passive learners to employ different learnercentred instructional and assessment practices that emphasise the responsibility of learning into actively engaging learners. By means of a structured questionnaire a small scale study (n=51) was done in urban, rural, township, and private schools in the North West and Gauteng provinces. The findings, inter alia, suggest that although History and Social Sciences teachers showed a willingness to utilise some of the learner-centred instruction strategies, their tendency to implement the traditional teacher-centred instruction strategies were much stronger. The findings further show that teachers preferred to be the primary assessors of the learning results.
Keywords: Learner-centred instruction strategies; History teaching; Social Sciences teaching; Teaching and learning; Assessment